Bubble Impingement and the Mechanisms of Heat Transfer - ROBINSON, ANTHONY; ALBADAWI, ABDULALEEM; MURRAY, DARINA (My University, 2014)
Heat transfer augmentation resulting from the effects of two phase flow can play a significant role in convective cooling applications. To date, the interaction between a rising gas bubble impinging on a heated horizontal surface has received limited attention. Available research has focused on bubble dynamics and the associated heat transfer has not been reported. To address this, this study investigates the effect of a single bubble impinging on a heated horizontal surface. Local and time resolved heat transfer measurements have been performed for a died orifice to surface distance, with a bubble injection orifice of 1 mm in diameter. Synchronized high-speed photography and infrared thermography have been utilized to investigate the path of the bubble and the associated heat transfer.
PUBLISHED
Keywords: Local heat flow; Bouncing bubble; Rising bubble